Electrocardiographic profile of asymptomatic adolescents by the TELE ECG system in Brazil: analysis of 11058 patients. (3rd October 2022) - Nogueira, M F; Andalaft, R; Hinkelmann Berbert, G; Valdigem, B; Pinto, V B C; Moretti, M P; Felicioni, S P; Fernandes, R C; Franca, F F A C; Freitas, R V; Feres, F
Abstract: Introduction: The search for markers that can serve as screening methods for young practitioners of physical activity has always raised an intense discussion between pediatricians and cardiologists. Thus, the ideal investigation algorithm should identify patients at high risk also among asymptomatic patients and be of low cost to society. This would only be possible by including a low cost diagnostic method and largely accessible. In this context, telemedicine systems and in particular tele-electrocardiogram (tele-EKG) systems have low cost and agility and can collaborate to solve this problem. Purpose: To analyze the electrocardiographic pattern in asymptomatic patients aged between 10 and 20 years old who underwent EKG by the tele-EKG system between 2007 and 2014 Methods: All EKG valid results from asymptomatic patients aged between 10 and 20 years old from 2007 and 2014 sent to the tele-EKG system of a large tertiary hospital were analysed aiming to determine the prevalence of abnormal findings. Results: Of the 797, 115 exams on the analysed period 25, 326 were from patients aged between 10 and 20 years old and 11, 058 (55% male) of them were asymptomatic. Regarding disorders of rhythm, ventricular arrhythmias were found in 0.54% and atrial premature beats in 0.47% of the exams. There were 5 episodes of supraventricular tachycardia (0.04%) and one episode of atrial fibrillation. Atrioventricular blocks were: first degree (0.71%) and second degree (0.03%). There was 1 case of 2:1 AV Block and 1 case of advanced AV block. Short PR interval was observed in 0.76% of the exams, with 15 of them showing ventricular pre-excitation (0.13%). Regarding morphological changes in EKG pattern, right bundle branch disorders were present in 7.5% of the patients and left bundle branch in 0.04%. Right bundle branch block occurred in 0.63% and left bundle branch block in only 1 case. Repolarization changes occurred in 1.8% of patients. We found left ventricular overload in 0.25% and right ventricular overload in 0.14% of cases. Only 5 patients had typical EKG of septal hypertrophy (0.045%). There were 1751 diagnostics overall, representing 15.8% of the sample. The most prevalent was right bundle branch abnormalities, followed by repolarization abnormalities (graphic below). Conclusion: EKG screening in asymptomatic adolescents is a low cost and feasible method to identify individuals with electrical alterations and who require detailed clinical evaluation. This also may contribute to reduce risk of sudden events during sports activities. Funding Acknowledgement: Type of funding sources: None.